An Annotated Guide to Tactics Carl von Clausewitz's Theory of the Combat - von Clausewitz, Carl (Marine Corps University Press (MCUP), 2021)
The philosophy on which the Marine Corps' seminal warfighting doctrine is based rests on a tradition of professional military scholarship that reaches back to Carl von Clausewitz's treatise On War. Clausewitz's lesser-known and often-misunderstood Guide to Tactics, republished here for the first time as a standalone English text with critical annotations, serves as the foundation of the Marine Corps' warfighting philosophy and provides a guide to thinking about the nature of tactics and combat for the modern warfighter.